NILAI KERJA PADA ANGGOTA TNI-AD BERDASARKAN TAHAPAN KARIR - Farah Army Jayanti; Yudi Suharsono; Tri Muji Ingarianti (Psympathic : Jurnal Ilmiah Psikologi, 2015)
The value of work is a person’s belief associated with his/her life achievement. This study aimed to investigate the most value of work that emerged in every career stage. The numbers of respondents were 400 people taken by using random sampling technique. Methods of data analysis used a quantitative descriptive. The results were the dominant work value appeared at each career stages. Based on age category, below 30 years-old, the dominant value of work was comfort, age of 31 years-old up to 44 years-old was principles of altruism, over 45 years- old was the value of status, and at the age above 55 years-old was achievement. In regard to the position level, the dominant work values across the levels namely for Tamtama was comfort, for Bintara was altruism, Bintara Tinggi was achievement and autonomy, and for Perwira was achievement.